2018
DOI: 10.3389/fpls.2018.01294
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Effector Pst_8713 Impairs the Plant Immunity and Contributes to Virulence of Puccinia striiformis f. sp. tritici

Abstract: Puccinia striiformis f. sp. tritici (Pst), the causal agent of stripe rust, is an obligate biotrophic pathogen responsible for severe wheat disease epidemics worldwide. Pst and other rust fungi are acknowledged to deliver many effector proteins to the host, but little is known about the effectors’ functions. Here, we report a candidate effector Pst_8713 isolated based on the genome data of CY32 and the expression of Pst_8713 is highly induced during the early infection stage. The Pst_8713 gene shows a low leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…The SP-SUC2 construct was generated by cloning the 22-aa SP of Orphan OSP1 OSP2 OSP3 OSP4 OSP5 OSP6 OSP7 OSP8 OSP9 OSP10 OSP11 OSP12 OSP13 OSP14 OSP15 OSP16 OSP17 OSP18 OSP19 OSP20 OSP21 OSP22 OSP23 OSP24 OSP25 OSP26 OSP27 OSP28 OSP29 OSP30 OSP31 OSP32 OSP33 OSP34 OSP35 OSP36 OSP37 OSP38 OSP39 OSP40 OSP41 OSP42 OSP43 OSP44 OSP45 OSP46 OSP47 OSP48 OSP49 Osp24 (Fig. 2d) into the vector pSUC2 40 and transformed into the yeast suc2 mutant 41 . The resulting SP-SUC2 transformants were able to grow on YPRAA agar and had secreted invertase activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SP-SUC2 construct was generated by cloning the 22-aa SP of Orphan OSP1 OSP2 OSP3 OSP4 OSP5 OSP6 OSP7 OSP8 OSP9 OSP10 OSP11 OSP12 OSP13 OSP14 OSP15 OSP16 OSP17 OSP18 OSP19 OSP20 OSP21 OSP22 OSP23 OSP24 OSP25 OSP26 OSP27 OSP28 OSP29 OSP30 OSP31 OSP32 OSP33 OSP34 OSP35 OSP36 OSP37 OSP38 OSP39 OSP40 OSP41 OSP42 OSP43 OSP44 OSP45 OSP46 OSP47 OSP48 OSP49 Osp24 (Fig. 2d) into the vector pSUC2 40 and transformed into the yeast suc2 mutant 41 . The resulting SP-SUC2 transformants were able to grow on YPRAA agar and had secreted invertase activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…P CaMV 35S -Osp24 ΔSP was cloned into pGR106 and transformed into A. tumefaciens strain GV3101 90 expressing the BAX and INF1 constructs 91 resuspended to OD 600 of 0.8 in infiltration solution (10 mM MES, 10 mM MgCl 2 , and 150 μM acetosyringone) 90 . At 18 h after the initial infiltration of tobacco leaves with A. tumefaciens transformant carrying the P CaMV 35S -Osp24 ΔSP construct, the same sites were infiltrated with cells carrying GFP, BAX, or INF1 constructs 40 . Plant cell death symptoms were examined 5 days after infiltration with cells expressing BAX or INF1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pst, Dagvadorj et al [29] reported that PstSCR1 can activate immunity in non-host plants. Zhao et al [30] found that Pst_8713 was involved in enhancing Pst virulence and suppressing plant immunity. Yang et al [31] identified that Pst18363 displayed an important pathogenicity factor in Pst.…”
Section: Introductionmentioning
confidence: 99%
“…For stripe rust, five candidate effectors were identified in four Pst isolates from the United Kingdom and the United States (21). In addition, PEC6, Pst_8713, PstGSRE1, and PSTha5a23 from Pst were demonstrated to impair plant immunity (22)(23)(24)(25). Nine candidate effectors from Pst and Puccinia graminis f. sp.…”
mentioning
confidence: 99%